Examining Strategies for Enhanced Inner City Traffic Management and Health Impacts: A Case Study of a Mumbai Street - Shetty, Neha Surendra (Digital Repository of Theses - SSBM Geneva, 2025)
This case study discusses the problem of inner-city traffic management and how it relates to health issues by using as an example one specific precinct of Mumbai, which is globally recognized as the city with the highest density of population and severe traffic jams. The aim of the study is to find not only the causes of traffic difficulties but also to find the ways of estimation of consequences and make decisions. The study analyses the traffic congestion issue from the viewpoint of physical and behavioural aspects of health and describes the social consequences of the problem of urban congestion both in the economy and the environment. In a combined method, the data was obtained by personal observations, interviews with the residents and commuters, and interviews with the healthcare professionals. The research points to the central factors of weak infrastructure, illegal intrusions, the phenomenon of seasonal flaunting during monsoons, and the continual growth of private vehicle ownership, that have resulted in congestion. The study also underscores the negative health effects of road traffic pollution on nearby residents, including respiratory diseases, high stress, and lower quality of life due to noise pollution. This study is looking to be part of a larger conversation about sustainable urban development. For this, it will be dealing with the existing problems of traffic congestion and public health. The findings are of special importance for cities such as Mumbai, among others. They have to face up to rapid urbanization and come up with quick, multifaceted as well as innovative solutions.